Bericht über die Gesetzgebungstätigkeit des Japanischen Parlamentes in der 163. und 164. Sitzungsperiode - Schimmann, Peter (Zeitschrift für Japanisches Recht, 2006)
The article provides an introduction to the most important laws enacted during the 163rd and 164th session of the Japanese Parliament. Tax law has been amended regarding income tax rates, tax bases for foreigners living in Japan and taxation of bonus payments to directors of corporations. An amendment to banking laws has expanded the possibilities for operating in the Japanese banking sector. One of the most important reforms concerns the Japanese Post, which will be divided in four business areas under a holding company and gradually privatized. The introduction is accompanied by an overview of all laws passed in Japanese (kanji and rôma-ji) and a German as well as an English translation. (The Editors